2017
DOI: 10.1017/s1368980017002579
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative study conducted in the USA exploring Latino fathers’ beliefs, attitudes and practices related to their young children’s eating, physical activity and sedentary behaviours

Abstract: Objective: Increasing evidence documents fathers' influential role in their children's eating, physical activity (PA) and sedentary behaviours (SB). We aimed to expand limited existing research examining fathers' influence in these areas by exploring Latino fathers' beliefs, attitudes and practices related to eating, PA and SB of their young children. Design: Seven focus group discussions were conducted in Spanish with Latino fathers (n 28) of children aged 2-8 years. Audio recordings were transcribed and tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
42
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(53 citation statements)
references
References 82 publications
7
42
0
1
Order By: Relevance
“…This is consistent with previous qualitative research, including our own, and indicates the importance of the family within Latino communities [28,30,50,51]. It also suggests that the family should be considered the unit of change and that interventions focusing on promoting healthy ST will likely be more successful if they consider the entire family unit, including adults (e.g., both parents, other relatives such as grandmothers) and children (younger and older children).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…This is consistent with previous qualitative research, including our own, and indicates the importance of the family within Latino communities [28,30,50,51]. It also suggests that the family should be considered the unit of change and that interventions focusing on promoting healthy ST will likely be more successful if they consider the entire family unit, including adults (e.g., both parents, other relatives such as grandmothers) and children (younger and older children).…”
Section: Discussionsupporting
confidence: 89%
“…Although more research is needed, it is worth noting that mothers participating in the present study reported that their husbands did not perceive their young children's ST behaviors as problematic and expressed minimal or no concerns for their preschoolaged children's ST. Additionally, most mothers reported their husbands watched TV and played video games with their children, which is consistent with prior research conducted among other populations [50,61]. This is important as research shows that children have increased ST when parents have ST themselves [50,[61][62][63][64].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Parents were eligible to participate if they: (a) self-identified as Central American; (b) had at least one child aged 11-19 years; (c) lived in MA or RI; and (d) had resided in the US for at least 12 months. We recruited participants using strategies successfully employed in our previous studies with similar Latino populations, and these included: (1) posting flyers inside local Latino businesses, and community-based social and health services agencies, and (2) making announcement and posting flyers at predominantly Spanish-speaking churches [30][31][32][33][34]. Interested individuals spoke to study staff at church events or called the telephone number listed on the flyers disseminated at local Latino businesses, community-based social and health services agencies, and churches.…”
Section: Ethics Consent and Permissionsmentioning
confidence: 99%
“…Qualitative studies found that Latino fathers valued the health and developmental benefits of physical activity and applied a variety of practices to engage in physical activity with their children and limit screen time [18][19][20]. However, Latino adolescents' perceptions of their fathers' parenting practices may differ from their fathers' perceptions.…”
Section: Introductionmentioning
confidence: 99%